Web-Based Supported Teaching Prototype : A Case of Nakhon Si Thammarat Rajabhat University - Wichit, Sookkhathon (2004)
Educational technology contributes to the effective result on teaching and learning. The information technology, especially the Internet, is creating tremendous opportunities for higher educational institutions. The web-based teaching and learning system, in particular, provides many benefits to students and teachers. This research aims to study and look into an appropriate model of web-based learning and teaching for the local universities. The purpose of this research is also to provide a prototype called “Web-based supported teaching”, which demonstrates the implications of the model. This study find that the database driven application with PHP and My SQL are appropriate tools for developing web-based supported teaching system. This study uses Nakhon Si Thammarat Rajabhat University as a case study. Nakhon Si Thammarat Rajabhat University is a local university in Nakhon Si Thammarat, Thailand. The main objective of web-based supported teaching prototype is to establish an effective tool to enhance a traditional classroom approach of the university. This research also evaluates the prototype by employs a personally administered questionnaire approach. There are 60 respondents both lecturers and students of Nakhon Si Thammarat Rajabhat University. The result indicates that all users are satisfied with this prototype. The conclusions will show the advantages and the possibility of the implementation of web-based supported teaching system for Nakhon Si Thammarat Rajabhat University.